PELAKSANAAN PEMBELAJARAN DALAM JARINGAN DI MASA PANDEMI COVID-19 PADA JENJANG SEKOLAH DASAR DI SD NEGERI 6 RAJA - Ilham Febri Budiman (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The Covid-19 pandemic has had a negative impact on education. Primary school is one of the levels that feel the impact of the Covid-19 pandemic. Education at the elementary school level is an initial milestone in the formation of student character, so that if done online the function of developing and monitoring educators becomes ineffective. This research aims to find out the impact of learning implementation on teachers and students at the elementary school level in SD Negeri 6 Raja. The method used in this study is a qualitative method obtained through interview activities directly to educators in SD Negeri 6 Raja. Broadly speaking, the results obtained illustrate that online learning in SD Negeri 6 Raja is very influential on educators and learners. There are more negative effects than positive effects. The benefit of this research is to enrich references about the implementation of online learning at the elementary school level, especially in areas outside Java.